Intersex Activism, Medical Power/Knowledge and the Scalar Limitations of the United Nations. (17th July 2022) - Garland, Fae; Lalor, Kay; Travis, Mitchell
Abstract: This article considers the extent to which human rights mechanisms can ameliorate intersex rights at a sub-national, or medico-local, level. It engages with both intersex activism and the academy where the United Nations (UN) has become understood as a key mechanism through which to challenge day-to-day practices of healthcare practitioners and bring an end to nontherapeutic surgical and hormonal interventions on intersex infants and children. Using the UK as an example, this article examines how and why the UN's engagement with intersex has had little effect on the medical regulation of intersex people. To do so, the article draws on legal geography to examine how scale prevents the UN from having a clear and lasting impact on domestic issues – particularly those in healthcare settings. The different ways in which intersex bodies are recognised and regulated at different scales, coupled with the UN's inability to form dialogue with the institutions of the state, such as the healthcare profession, are problematic barriers to challenge practice at the medico-local scale.